The use of the Scleroderma Clinical Trials Consortium Damage Index in systemic sclerosis - L. P. Ananyeva; V. V. Babak; A. D. Koltakova; O. A. Koneva; O. V. Desinova; M. N. Starovoytova; O. B. Ovsyannikova; R. U. Shayakhmetova (Научно-практическая ревматология, 2025)
Background. The assessment of organ damage in patients with systemic sclerosis (SSc) is challenging. The Scleroderma Clinical Trials Consortium Damage Index (SCTC-DI) proposed in 2019 has not been sufficiently studied and requires testing for wider use.The aim of the study was to examine the progression of organ damage in patients with systemic sclerosis assessed by SCTC-DI during a one-year prospective follow-up.Materials and methods. A prospective observational study was performed, within the framework of which the SCTC-DI was assessed twice with an interval of 12 [10; 14] months in 74 adult patients (62 (84%) women) with SSc with an average age of 48±13 years. SSc was classified according to the criteria of progressive systemic sclerosis and in 43 (58%) cases was represented by a limited form. The duration of the disease was 92 [47; 164] months. The inclusion criterion was SCTC-DI≥1 point for at least one of 23 indicators at one of the assessment points. Statistical data processing was performed using parametric and nonparametric analysis methods.Results of the study. At inclusion in the study, the median (Me) of the SCTC-DI was 7.5 [4; 12] points (min–max: 0–23). 27 (36%) patients initially had a low degree of damage (SCTC-DI≤5), the rest had moderate or severe damage. Upon repeated assessment, the Me of SCTC-DI decreased to 7 [4; 10] points (min–max: 0–17; p=0.023). After one year, there was a significant decrease in the incidence of digital ulcers, clinical signs of esophageal hypotension and symptoms of gastroesophageal reflux disease (GERD). At the same time, the incidence of myocardial disease associated with SSc increased (p<0.001). There was also a decrease in the median vascular and gastrointestinal tract damage scores (p<0.001), and an increase in the median cardiovascular score (p=0.027). The decrease in the total SCTC-DI score was statistically associated with the use of oral glucocorticoid therapy during the study period (p=0.011), as well as cyclophosphamide anamnesis (p=0.015).Conclusion. The SCTC-DI was proposed for an objective assessment of changes in the condition of patients with SSc and takes into account irreversible changes in the main manifestations of the disease, which is reflected in an increase in the index value over time. In this study, the total SCTC-DI slightly but reliably increased with a multidirectional change in the values of individual index components. The use of the DI revealed certain of its shortcomings, which impose significant restrictions on its use in practice and mean the need for further work on validating the DI and more precise definitions of the main indicators of irreversible damage.